2020
DOI: 10.1002/we.2395
|View full text |Cite
|
Sign up to set email alerts
|

Parametric dependencies of the yawed wind‐turbine wake development

Abstract: Yaw misalignment is currently being treated as one of the most promising methods for optimizing the power of wind farms. Therefore, detailed knowledge of the impact of yaw on the wake development is necessary for a range of operating conditions. This study numerically investigates the wake development behind a single yawed wind turbine operating at different tip-speed ratios and yaw angles using the actuator-line method in the spectral-element code Nek5000. It is shown that depending on the tip-speed ratio, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…First, the interaction between wake rotation and the ground has been shown to substantially influence the vertical displacement of the wake centre during yaw (Bastankhah & Porté-Agel 2016). Furthermore, Kleusberg, Schlatter & Henningson (2020) showed that the angle of attack of the blades varies between the top and bottom of the rotor when the turbine is yawed, introducing an additional source of vertical asymmetry. Finally, differences in spanwise vorticity between the top and bottom of the rotor may contribute to changes in the vertical velocity field of the wake.…”
Section: Resultsmentioning
confidence: 99%
“…First, the interaction between wake rotation and the ground has been shown to substantially influence the vertical displacement of the wake centre during yaw (Bastankhah & Porté-Agel 2016). Furthermore, Kleusberg, Schlatter & Henningson (2020) showed that the angle of attack of the blades varies between the top and bottom of the rotor when the turbine is yawed, introducing an additional source of vertical asymmetry. Finally, differences in spanwise vorticity between the top and bottom of the rotor may contribute to changes in the vertical velocity field of the wake.…”
Section: Resultsmentioning
confidence: 99%
“…2017; Mühle et al. 2018; Kleusberg 2019; Kleusberg, Schlatter & Henningson 2020). Since the focus of those studies was on the wake and on total forces, the errors caused by the approximation of the tip correction were not considered to greatly affect the results.…”
Section: Methodsmentioning
confidence: 99%
“…The actuator line was previously implemented in Nek5000 (Kleusberg et al 2016, 2017, Kleusberg 2019) with Prandtl's tip correction. The code was extensively validated, showing good agreement between numerical and experimental results (Kleusberg et al 2017, Mühle et al 2018, Kleusberg 2019, Kleusberg et al 2020. Since the focus of those studies were on the wake and on total forces, the errors caused by the approximation of the tip correction were not considered to greatly affect the results.…”
Section: Numerical Solver Of Navier-stokes Equations With the Actuato...mentioning
confidence: 99%